Intraoperative assessment of femoral head perfusion during surgical hip dislocation for slipped capital femoral epiphysis. Issue 4 (8th April 2021) - Michalopoulos, Adrian; Spelman, Christopher; Balakumar, Jitendra; Slattery, David
Abstract: Avascular necrosis is the most devastating complication of slipped capital femoral epiphysis, leading to collapse of the femoral head, increased risk of osteoarthritis and the requirement of early total hip arthroplasty. It is believed that intraoperative femoral head perfusion assessment may be an accurate predictor of post-operative avascular necrosis (radiographic collapse). At our institution, femoral head perfusion is assessed intraoperatively during all sub-capital realignment procedures. We hypothesize that our method is accurate in predicting the risk of developing post-operative avascular necrosis. In this retrospective study, we collected data from all patients that had intraoperative blood flow measurements during sub-capital realignment procedures. We correlated this with long-term radiographs looking for radiographic collapse. The intraoperative femoral head perfusion assessments during sub-capital realignment procedures for slipped capital femoral epiphysis at our institution, between January 2015 and March 2020 inclusive were assessed for reliability. In total, 26 of 35 patients had intraoperative femoral head perfusion present. Only 2 (8%) of these patients developed radiographic collapse. In contrast, 7 (78%) of the 9 patients who did not have femoral head perfusion present intraoperatively developed radiographic collapse, indicating that our method may be reliable in predicting a patient's post-operative risk of developing avascular necrosis.